Chronic myeloid leukemia data from India - Shweta Bansal; Kumar Prabhash; Purvish Parikh (Indian Journal of Medical and Paediatric Oncology)
In an effort to collaborate the data of chronic myeloid leukemia (CML) patient from all over India,meeting was conceived by ICON ( Indian Cooperative Oncology Network) in 2010. This article presents the summarized picture of the data presented in the meeting. In the meeting 8115 patients data was presented and 18 centres submitted their manuscripts comprising of 6677 patients. This data represents large series of patients from all over the country treated on day to day clinical practice and presents the actual outcomes of CML patients in India. The compilation of data confirms the younger age at presentation, increased incidence of resistance and poor outcomes in patients with late chronic phase. It also addresses the issues like Glivec versus Generic drug outcomes, safety of Imatinib during pregnancy and mutational analysis among resistant patients. It concludes that survival and quality of life of CML patients in India has improved over the years especially when treated in early chronic phase. The generic drug is a good option where original is unable to reach the patient due to various reasons. Hopefully, this effort will provide a platform to conduct systematic studies in learning the best treatment options among CML patients in Indian settings.